Evaluating the iron chelator function of sirtinol in non-small cell lung cancer - Petronek, Michael S.; Bayanbold, Khaliunaa; Amegble, Koffi; Tomanek-Chalkley, Ann M.; Allen, Bryan G.; Spitz, Douglas R.; Bailey, Charvann K. (Frontiers in Oncology, 2023)
A distinctive feature of cancer is the upregulation of sirtuin proteins. Sirtuins are class III NAD+-dependent deacetylases involved in cellular processes such as proliferation and protection against oxidative stress. SIRTs 1 and 2 are also overexpressed in several types of cancers including non-small cell lung cancer (NSCLC). Sirtinol, a sirtuin (SIRT) 1 and 2 specific inhibitor, is a recent anti-cancer agent that is cytotoxic against several types of cancers including NSCLC. Thus, sirtuins 1 and 2 represent valuable targets for cancer therapy. Recent studies show that sirtinol functions as a tridentate iron chelator by binding Fe3+ with 3:1 stoichiometry. However, the biological consequences of this function remain unexplored. Consistent with preliminary literature, we show that sirtinol can deplete intracellular labile iron pools in both A549 and H1299 non-small cell lung cancer cells acutely. Interestingly, a temporal adaptive response occurs in A549 cells as sirtinol enhances transferrin receptor stability and represses ferritin heavy chain translation through impaired aconitase activity and apparent IRP1 activation. This effect was not observed in H1299 cells. Holo-transferrin supplementation significantly enhanced colony formation in A549 cells while increasing sirtinol toxicity. This effect was not observed in H1299 cells. The results highlight the fundamental genetic differences that may exist between H1299 and A549 cells and offer a novel mechanism of how sirtinol kills NSCLC cells.